2010
DOI: 10.1177/0194599810390917
|View full text |Cite
|
Sign up to set email alerts
|

Video Pneumatic Otoscopy for the Diagnosis of Conductive Hearing Loss With Normal Tympanic Membranes

Abstract: The VPO is a simple, noninvasive, and accurate tool for the differential diagnosis of CHL with a normal TM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 12 publications
(17 reference statements)
0
11
0
1
Order By: Relevance
“…12,16 The use of video-pneumatic otoscopy may address the difficulty in identifying a retracted tympanic membrane while being appropriate for use within a hearing telehealth clinic. 26,27 Using video-pneumatic otoscopy and quantitative analysis of the degree of movement of the umbo of the malleus, Cho et al 27 reported correlation between tympanograms and, among other middle ear pathologies, negative middle ear pressure. Although otitis media with effusion may occur spontaneously because of negative middle ear pressure, 28 the identification of a retracted tympanic membrane may not be highly significant within a primary healthcare environment in a rural or underserved area.…”
Section: Video-otoscopy With Telehealth Facilitatormentioning
confidence: 99%
“…12,16 The use of video-pneumatic otoscopy may address the difficulty in identifying a retracted tympanic membrane while being appropriate for use within a hearing telehealth clinic. 26,27 Using video-pneumatic otoscopy and quantitative analysis of the degree of movement of the umbo of the malleus, Cho et al 27 reported correlation between tympanograms and, among other middle ear pathologies, negative middle ear pressure. Although otitis media with effusion may occur spontaneously because of negative middle ear pressure, 28 the identification of a retracted tympanic membrane may not be highly significant within a primary healthcare environment in a rural or underserved area.…”
Section: Video-otoscopy With Telehealth Facilitatormentioning
confidence: 99%
“…Among patients with CHL, the differential diagnosis in cases with intact tympanic membrane (TM) can be challenging to clinicians, as no absolute diagnostic test is available for these patients [1,2]. To improve the preoperative diagnosis in CHL cases with intact TM, a variety of approaches have been evaluated, such as multi-frequency tympanometry [3], sweep frequency tympanometry [4], the liquid and acoustic reflex test [5], and pneumatic otoscopy [6]. Several approaches have revealed positive results in predicting the diagnosis of CHL; however, the results have been unsatisfactory for application to clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the pneumatic‐induced motions of the human TM were quantitatively assessed in vivo using a custom‐developed OCT system that resembles a pneumatic otoscope, the guideline recommended diagnostic tool for OM. Previous efforts to quantify the pneumatic movements of the TM involved tracking the positions of the TM structures (the umbo and the handle of malleus) during video pneumatic otoscopy [30, 31] and estimating the movements in pixels during video pneumatic otoscopy combined with a motion magnification algorithm [32]. However, quantification of standard pneumatic otoscopy still suffers from insufficient information about the axial movements and the structural variability of the human TM.…”
Section: Discussionmentioning
confidence: 99%